The role of healthy personality, psychological flexibility, and coping mechanisms in university students’ mental health in China - Xiao Yang; Xiao Yang; Kartini Ilias; Kartini Ilias; Khairil Anuar Md Isa; Qing-hong Li; Hai-bin Wang; Huan Li (Frontiers in Psychology, 2025)
BackgroundMental health issues such as anxiety and depression have become increasingly common among Chinese university students, especially after the COVID-19 pandemic. This study explores the relationships between personality health, psychological flexibility, coping styles, and mental health in this population.MethodsA cross-sectional survey was conducted with 2,528 university students (aged 18–25, 53.26% male). Personality was assessed using the MMPI, psychological flexibility via the AAQ and CFQ-F, and coping styles using the SCSQ. Mental health outcomes were gathered as part of a university-wide assessment.ResultsAfter controlling for demographic variables, personality health, psychological flexibility, and coping styles were significantly associated with mental health. Psychological flexibility showed a moderate correlation (r = 0.454–0.660, p < 0.001). The final multivariate model, including psychological flexibility and coping styles, explained a moderate portion of variance in mental health (Adjusted R2 = 0.4892, p < 0.001).ConclusionPsychological flexibility and adaptive coping strategies play a key role in promoting mental health among university students. Targeted interventions in these areas—such as integrating them into university curricula and support programs—can help mitigate anxiety and depression. Though based on a Chinese sample, the findings align with global research, highlighting the cross-cultural relevance of psychological flexibility in mental health interventions.